Analysis of long-term optical performance of phosphorescent oxygen sensing polymeric nanofibers. (December 2019) - Presley, Kayla; Shahhosseini, Melika; Shi, Dianne; Castro, Carlos; Lannutti, John
Abstract: Photostability assessments of polymeric optical oxygen sensors are typically of limited duration (orders of magnitude lower than real application durations), involve irreproducible setups, ignore sensitivity changes and evaluate a limited number of samples. Using custom LED aging bays, continuous photobleaching (>1 month) was used to assess oxygen-sensitive polysulfone-polycaprolactone core-shell electrospun nanofibers with incorporated platinum (II)- or palladium (II)-based porphyrins. Increased [porphyrin] corresponded to greater initial brightness and more rapid photobleaching. Nevertheless, the rapid solvent evaporation characteristic of electrospinning allowed for linear Stern-Volmer plots for solids loading as high as 10 wt%. UV excitation resulted in a greater initial photobleaching rate for both brightness and sensitivity, but these decreases ended after 1 week; green-aged samples continued to photobleach out to 1000 h. Via straightforward monitoring of brightness, oxygen sensitivity and Stern-Volmer linearity, this long-term photobleaching assessment protocol can be used to screen dozens of polymer sensors for real-life applications. Highlights: Methodology developed to enable high throughput aging of polymeric oxygen sensors. Evaluated long-term (>1 month) performance of oxygen sensing nanofibers. Performance and Stern-Volmer plot linearity readily assessed versus aging time. LED wavelength and porphyrin concentration shown to affect photostability. Photobleaching plateaued after 1 week for UV-aged polymer nanofibers.